(3GbQ GHGPjfGJs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb aShi hHYO gPg fSN aj CbQHGPjfGJ bO hbY YdGLI heOGhJg ddCUMGH hGdCMHGH aLQHfGg s
(3BNQgG (B:s
( (3BNQ UaMGJgG JMJhi Ydi COhjI eaQOI hebOGQ TQHgG (B) s
(3HgG fXGe GdJYbjHIs
(3GdfSNI eXdeI Edi MO eGs
(3ai BNQ UaMGJ JMJhi Ydi ahGFO WHjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs